Study Review On Cultural Tourism, Participation, And Community Strengthening in Tourism Development - Mertayasa, I Gede Agus; Edy, Raden Agus Sarwa; Wiratanaya, Gede Nyoman; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2021)
This essay deal with a study review on cultural tourism, participation, and community strengthening in tourism development. The definition of cultural tourism under discussion is still under debate by anthropologists who are doing some research. Essentially some of these experts talk about the same goal, namely the existence of communities with their participation in the cultural process, the existence of foreigners or tourists who interact with the culture of the local community with all its consequences, the existence of efforts to local communities to strengthen, even at the center of the discussion, they are looking for new formulas. to balance the process of cultural globalization and cultural localization, which both have to deal with each other, whereby the process of cultural globalization brings with it the consequence of the formation of cultural homogeneity in all parts of the world, while the globalization process also has cultural heterogeneity as a unique factor so that a conserving and sustainable localization process is required.